Assessing efficiency of urban waste services and the role of tariff in a circular economy perspective: An empirical application for Italian municipalities. (10th November 2021) - Lombardi, Ginevra Virginia; Gastaldi, Massimo; Rapposelli, Agnese; Romano, Giulia
Abstract: Since the previous decade, there has been an increasing awareness regarding the crucial role of waste management efficiency in ensuring health and environmental protection and the transition toward circular economy objectives. This empirical study investigates the efficiencies of urban waste systems in 78 major Italian towns between 2014 and 2018, taking into account the waste reduction and recycling targets indicated by European circular economy strategy. To this end, we employed the nonparametric approach to measure efficiency, namely the data envelopment analysis (DEA) model. Two DEA models to account for both constant and variable returns to scale were performed. An undesirable output (the total amount of waste collected) was included in the analysis as an input to account for waste reduction targets. Moreover, efficiency scores obtained through the DEA analysis were investigated in relation to relevant variables, along with the already studied variables, such as geographic localization, population density, and the aging index. We also included the tariff paid for waste services and the collection method. The estimated efficiency scores showed significant differences across all the evaluated municipalities, with a promising average growth. We find that the Northern and Central major towns have higher efficiency than the Southern and Island towns. Moreover, efficiency is higher for more densely populated towns and towns with a higher elderly rate. Further, efficiency is higher when the average tariff applied is lower and when door-to-door collection is in force. Finally, the collection method emerges as a crucial issue in ensuring the transition toward circular economy in the urban waste sector.